Consumption of Herbal Supplements or Homeopathic Remedies to Prevent COVID-19 and Intention of Vaccination for COVID-19 in Latin America and the Caribbean - Bendezu-Quispe, Guido (2022)
Users of complementary and alternative medicine (CAM) have a lower intention to receive vaccines. Furthermore, Latin America and the Caribbean (LAC) region are among the most affected areas by the COVID-19 pandemics and present a high proportion of CAM users. Therefore, this study evaluates the association between the consumption of herbal supplements or homeopathic remedies to prevent COVID-19 and the intention to vaccinate against COVID-19 in the LAC region. We conducted a secondary data analysis of a Massachusetts Institute of Technology (MIT) survey with Facebook to assess COVID-19 beliefs, behaviours, and norms. Crude and adjusted prevalence ratios (aPR) with their respective 95% confidence intervals (95% CI) were calculated using generalized linear models of the Poisson family with the log link function. The prevalence of the use of products to prevent COVID-19 was the following: consumption of herbal supplements (7.2%), use of homeopathic remedies (4.8%), and consumption of garlic, ginger, and lemon (11.8%). An association was found between using herbal supplements (19.0% vs. 12.8%; aPR = 1.44; 95% CI: 1.30–1.58), the use of homeopathic remedies (20.3% vs. 12.3%; aPR = 1.58; 95% CI: 1.25–1.98), and the consumption of garlic, ginger, and lemon (18.9% vs. 11.9%; aPR = 1.55; 95% CI: 1.50–1.61) and non-intention to vaccinate against COVID-19. In the LAC population, there is an association between using herbal supplements, using homeopathic remedies and consuming garlic, ginger, and lemon to prevent infection by COVID-19 and non-intention to vaccinate against this disease. Therefore, it is necessary to design targeted strategies for groups that consume these products as preventive measures against COVID-19 to increase vaccination coverage and expand the information regarding transmission and prevention strategies for SARS-CoV-2.